Verticalising the multi-level analysis of urban and spatial development across geographies - Milbert, Antonia; Mueller, André; Kundu, Debolina; Sharma, Pragya (European Spatial Research and Policy, 2023)
Making the analysis of urban and spatial development more acceptable by all levels of analysis and governance requires a multi-level – or in other words vertical – approach to indicators measuring development paths. The 2030 Agenda of the United Nations with its 17 Sustainable Development Goals offers a promising chance to establish, maintain, and further develop a monitoring system that is supported by all levels involved, as well as all stakeholder groups and individuals across all levels. First experiences gathered in a nation (Germany) and bilateral and supranational context (Germany, Europe, and India) deliver recommendations for research and practice, and might thus show a possible way to attain successfully this goal.